2020
DOI: 10.3390/ijms21186482
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transforming Growth Factor-Beta in Retinal Ganglion Cells with Hyperglycemia and Oxidative Stress

Abstract: A characteristic of diabetes mellitus is hyperglycemia, which is considered with an emphasis on the diabetic retinopathy of progressive neurodegenerative disease. Retinal ganglion cells (RGCs) are believed to be important cells affected in the pathogenesis of diabetic retinopathy. Transforming growth factor-beta (TGF-β) is a neuroprotective protein that helps to withstand various neuronal injuries. To investigate the potential roles and regulatory mechanisms of TGF-β in hyperglycemia-triggered damage of RGCs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
2
14
0
2
Order By: Relevance
“…In this study, we found that the cell variability of RGCs is significantly lower in the 50 mM to 150 mM and the linear declined trend was evidence from 5.5 mM to 150 mM, which is consistent with previous studies [ 41 ]. RGCs were further labeled with neurons and RGC-specific markers TUJ1 and BRN3A, respectively, followed by the ImageJ quantitative analysis [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that the cell variability of RGCs is significantly lower in the 50 mM to 150 mM and the linear declined trend was evidence from 5.5 mM to 150 mM, which is consistent with previous studies [ 41 ]. RGCs were further labeled with neurons and RGC-specific markers TUJ1 and BRN3A, respectively, followed by the ImageJ quantitative analysis [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…ALDH3A1 can oxidize various aldehydes to their corresponding acids and is involved in the detoxification of alcohol-derived acetaldehyde and metabolism of corticosteroids, biogenic amines, neurotransmitters, and lipid peroxidation. The expression of ALDH3A1 is suggested to play an important role in the stress response and the anti-oxidation pathway for the protection of RGCs, transforming growth factor-beta in the treatment of diabetic retinopathy [47,48] and corneal cells against ultra-violet damage [49]. Our local network clusters analysis also indicated that there is an interaction between Aldh3a1, Oplah, and Mgst3, which are also believed to be related to the glutathione metabolic process.…”
Section: Discussionmentioning
confidence: 57%
“…However, sulfur antioxidants prevent necroptosis of RGC-5 cell lines by eliminating reactive oxygen species [ 37 ]. These drugs protect cells by blocking the signaling pathway that causes necroptosis from the beginning [ 38 ]. However, few experiments have been conducted on either of the drugs in vivo [ 39 ].…”
Section: Discussionmentioning
confidence: 99%